Rupture of an ice mound near Cape Dorset, N.W.T. - Frederking, R. M. W. (Canadian Geotechnical Journal, 1979)
An ice feature comprising ice blocks ranging from football size to 0.6 m cubes to 1.2 m × 3.6 m × 0.6 m slabs was observed on the surface of a frozen lake. Site investigations revealed the source of the blocks to be an ice mound that had formed along the shore of the lake. A model, supported by local meteorological, geological, and hydrological information, is proposed to explain the formation of the ice mound and its subsequent rupture.